Biochemical studies on antibiotic production from Streptomyces griseus - Talib Saleh Al-Rubaye; Bayader Abdel Mohsen; Shams Ahmed Subhi; Mohsen Hashem Risan (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
The present study was aimed for identify Streptomyces griseus by biochemical tests. All Streptomyces spp. isolates (MH1, MH7, MH3, MH17, MH25) were screened for their antibacterial activity using scross-streak technique against Gram-negative (Pseudomonas aeruginosa and Escherichia coli) and Gram-positive (Staphylococcus aureus). Screening was performed by agar-well diffusion method and growth inhibition zones were measured in millimeters for each of the Streptomyces spp. isolates MH1, MH7, MH3, MH25. Tested isolates have shown potent in vitro antibacterial activities against all tested pathogens. The highest activities were shown by isolate MH7 against Staphylococcus aureus (21 mm), Pseudomonas aeruginosa (17.8 mm), Escherichia coli (22.5 mm). Streptomyces spp isolates (MH1, MH7, MH3, MH25) were selected for biochemical studies. All isolates hydrolyzed starch. All isolates produced Catalase, Gelatinase, Protease, Urease, Amylase, Cellulase, Chitinase and Lipase. All Streptomyces spp. isolates have ability to reduce nitrate, Tyrosine degradation and Casein hydrolysis. Hydrogen sulphide (H2S) production, Oxidase production, Indole production and Melanine reaction were studied for Streptomyces spp. isolates(MH1, MH7, MH3, MH25). Most of the isolates were not H2S producer, Oxidase, Indole and Melanine reaction except one isolate (MH3). All Streptomyces spp. isolates could Citrate utilization and Pectin degradation except MH7. Streptomyces spp. isolates 4 isolate utilizes eight carbon sources (Carbohydrates utilization)such as the Glucose, Galactose, Fructose, Sucrose, Xylose, Maltose, Lactose and Mannitol). Results of Streptomyces spp. isolates by Utilization of nitrogen (amino acid) sources (L- arginine ,L-isoleucine, Lcysteine, L-glycine, L-tyrosine and L-alanine). Four Streptomyces spp. isolates were selected, characterized based and identified by biochemical examination according to Bergey’s Manual of determinative bacteriology. The bacteria was described to genus Streptomyces and species griseus. Given 4 isolates are presumptively the same or similar species (e.g., Streptomyces griseus). All isolates to have possessed similar biochemical tests results as the ones that were Streptomyces griseus.